PEMBERDAYAAN SUMBER DAYA MANUSIA UNTUK MENINGKATKAN KESEJAHTERAAN DAN KEMANDIRIAN DESA CUMEDAK - Abdul Rohim, Muhamat; Rahul Efendi, Muhammad; Hadi, Syukron; Firmansyah, Roni; Nasiroh, Holifatun; Afrik Rozana, Berliana; Maisyaroh, Shohifatul; Fisesa, Dian; Akrianti, Tiara; Dwi Susanto, Fajar; Faruq, Umar; Jannah, Yulisatul; Risqi Nurhasanah, Selvina; Regilia Putri, Maydina; Taufik Hidayat, Achmad; Padma Widhah, Cindy (Institut Teknologi dan Sains Mandala, 2024)
This community service in the form of Real Work Lectures (KKN) has the main purpose to improve the quality of life of the society in the KKN placement village area namely Cumedak Village Sumberjambe District. The quality of life of the society is related to various things, such as quality of food, health, welfare, etc. The stunting rate in Cumedak Village is quite high, which has an impact on the quality of life of the society. To overcome the problems in Cumedak Village especially stunting, KKN Collaborative students from group 200 carried out community service activities in 3 stages, that are field survey/observation, forming of work programs, and program implementation. The targets of this work program are stunted children, pregnant women, school children, and teenagers. There are 3 work programs that have been formed in order to prevent an increase of stunting rates in the Cumedak Village society, that are education on stunting and nutritious food, education of early marriage, and a healthy canteen program. The results of the KKN Collaborative group 200 student work program are increasing the insight and awareness of the Cumedak Village society regarding stunting, nutritious food, and marriage at sufficient age. It is hoped that this increased understanding and awareness will have an impact on reducing stunting rates and improving the quality of life of the Cumedak Village society.